Pitching 2.0: conceptualization and develpment in crowdfunding projects - Martín-Núñez, Marta (Historia y Comunicación Social, 2014)
Crowdfunding sites invert the traditional film production process selling audiovisual projects directly to end consumers through videos and written information. In this paper we aim to conceptualize the concept of pitching 2.0 and its development in this context through the analysis of audiovisual projects in the Spanish site Verkami.
Keywords: Crowdfunding; film production; web 2.0; funding; Internet; verkami